Investigating BMI, fatphobia and dietary habits of individuals going to the gym - Eroglu, Erdem; Yavuz Eroglu, Sultan (Progress in Nutrition, 2020)
Study Objective: The purpose of this study was to investigate BMI, fatphobia, and dietary habits of individuals going to the gyms. Methods: Samples of this study consisted of individuals who go to the gyms in Siirt province. The sample size consisted of 514 individuals(190 female, 324 male) who participated voluntarily in the study. A survey method was used as a data collection method in the study. To determining the fatphobia levels of participants, a 14 item scale developed by Scheltema and Robinson (2001) was conducted. Questions from the survey prepared by Ceylan (2017) were used for determining demographic attributes and dietary habits of participants. In the comparison of continuous data between two independent groups t-test was used and one way ANOVA test was used for comparison of continuous data between independent groups which are more than two. Scheffe test was used as a post-hoc analysis for determining the differences after the test Anova. Pearson correlation analysis was conducted between the continuous variables of the study. Result: As a result of the study, there was no significant relationship between BMI and fatphobia. However, when the differentiation status of BMI and fatphobia values ​​according to their nutritional habits were observed, it was found that there was a significant difference in favor of those who exercise for weight loss (p <0.05).